Analisis Kesiapan Pedagogis Dan Teknologis Guru Dalam Mengadopsi Ai Sebagai Sarana Pembelajaran Adaptif - Zaki, Ahmad Rifian Maula; Ulya, Indana Ainiya (Publikasi Indonesia, 2025)
The development of artificial intelligence (AI) technology increasingly opens up opportunities for the transformation of education towards a more adaptive learning approach. However, the readiness of teachers as the main actors in the education ecosystem is a determining factor in the adoption of this technology, especially in creating adaptive learning. This study aims to measure the level of teacher readiness in utilizing AI as an adaptive learning assistant, focusing on pedagogical, technological, and AI adoption aspects. This study used a quantitative method with a survey approach to 42 English teachers at the junior high school level in Semarang Regency. Data were analyzed using descriptive analysis and correlation analysis. The results showed that teachers' pedagogical readiness level was in the high category, while the aspect of teachers' technological readiness was the most significant variable in supporting readiness in adopting AI. Findings from this study also showed that teachers have a general interest in AI with their pedagogical and technological abilities. The researcher of this study suggested significant training and professional development to facilitate teachers in adopting AI in adaptive learning of English subjects effectively and efficiently.